Parenting Styles in Gifted and Talented Muslim Families: A Systematic Literature Review - Ningrum, Ratri Wahyu; Syafril, Syafrimen (International Journal of Islamic Studies Higher Education, 2024)
This study aims to analyze parenting patterns of gifted and talented children through a Systematic Literature Review approach. Gifted children have above-average intelligence (IQ > 130) which requires special parenting so that their potential can develop optimally. This research highlights the challenges faced by parents, including the unsynchronized cognitive, social and emotional development of gifted children, and how social, cultural and economic contexts influence parenting approaches. The results of the literature review indicate that authoritative parenting is the most effective parenting style for gifted children, combining high demands with strong emotional support. Research also found that cultural differences, such as collectivist orientation in Asia and individualism in the West, influence parenting patterns. On the other hand, limited economic resources are a significant challenge in the care of gifted children, especially in developing countries such as Indonesia. This study identifies a gap in the literature in Indonesia related to parenting gifted children, although many similar studies have been conducted in developed countries. By analyzing 23 international studies, this research provides new insights into parenting of parents of gifted children in the Indonesian context. The results of this study are expected to contribute to the development of the theory and practice of parenting gifted children, as well as assist parents, educators and policy makers in supporting the optimal development of gifted children.